To find the length between the two points (0, 6) and (-3, -2), we can use the distance formula, which is derived from the Pythagorean Theorem.
The distance formula is:
d = √((x2 - x1)^2 + (y2 - y1)^2)
Plugging in the coordinates of the two points:
d = √((-3 - 0)^2 + (-2 - 6)^2)
= √((-3)^2 + (-2 - 6)^2)
= √((-3)^2 + (-8)^2)
= √(9 + 64)
= √73
Rounding to the nearest hundredth, the length between the two points is approximately 8.54 units.
Apply the Pythagorean Theorem to find the length between (0, 6)%0D%0A(%0D%0A0%0D%0A,%0D%0A %0D%0A6%0D%0A)%0D%0A and (−3, −2)%0D%0A(%0D%0A−%0D%0A3%0D%0A,%0D%0A %0D%0A−%0D%0A2%0D%0A)%0D%0A. Round your answer to the nearest hundredth, if necessary.
1 answer